A deterioração das relações Brasil / Estados Unidos e a missão Albino Silva (outubro 1962) - Assis, Jamily Silva de (2020)
This dissertation analyzed Brazil's participation in the Missile Crisis (October 1962). The reaction of the Latin American countries and the Brazilian vote in the Organization of American States (OAS) and the Albino Silva Mission are briefly portrayed. The objective, mainly, is to understand how the actions of the Brazilian government during the Missile Crisis and, specifically, the execution of the Albino Silva Mission led to the deterioration of Brazil- United States relations. It discusses how the ambiguity of the João Goulart government and its attempt to highlight the Independent Foreign Policy (PEI), along with national public opinion, through the Albino Silva Mission and the double game between Washington and Moscow, which came to be taken in the period. Confidential and secret sources were used, such as telegrams, letters, memos and minutes of meetings of the Brazilian and American governments. This dissertation relies on confidential and secret sources from the archives of the Brazilian Foreign Ministry.